Etiology and prognosis of non-immune hydrops fetalis: A literature review (Research, Society and Development, 2024)
Introduction: Hydrops Fetalis is defined as an abnormal accumulation of fluid in the fetal compartments. It is estimated that 1 in 1,700 to 3,000 pregnancies are affected by this pathology. It can be subdivided into isoimmune or non-immune. The non-immune cause corresponds to 90% of cases and has variable etiopathogenesis. The prognosis varies according to the etiology. Method: Literature review with searches in the PubMed and Scielo databases, according to the guiding question: "What is the etiological cause and prognosis of patients affected by non-immune Hydrops Fetalis?". Results and Discussion: Hydrops Fetalis is a rare condition with a high morbidity and mortality rate. Regarding the etiology, cohort studies show that most cases diagnosed in the first trimester have genetic abnormalities as the main cause, with the main associated syndromes being Down, Turner and Edwards syndrome. In the second and third trimesters, hematologic diseases stood out, with thalassemia, followed by cardiac alterations and congenital infections. All causes of fetal hydrops were associated with fetal death, premature birth, and neonatal losses. Conclusion: The studies discussed in this review showed that the main etiologic causes related to non-immune FH are genetic, hematologic, and cardiac abnormalities. The higher the gestational age at diagnosis, the better the prognosis. Studies establishing management/counseling protocols are encouraged.